A concise review of the brown seaweed Sargassum thunbergii — a knowledge base to inform large-scale cultivation efforts - Fu-Li Liu; Jing-Jing Li; Zhou-Rui Liang; Quan-Sheng Zhang; Feng-Juan Zhao; Alexander Jueterbock; Alan T. Critchley; Stephen L. Morrell; Jorge Assis; Yong-Zheng Tang; Zi-Min Hu (Journal of Applied Phycology, 2021)

Occurrence, source apportionment, and carcinogenic risk assessment of polycyclic aromatic hydrocarbons in urban road dusts in Shanghai - Xue-Tong Wang; Rui Fu; Ying Zhou; Cheng-Lin Wang; Guo-Fa Ren; Xiao-Li Wang; Hui Li (Environmental Science and Pollution Research, 2021)

Tracing Nutrients and Organic Matter Changes in Eutrophic Wenchang (China) and Oligotrophic Krka (Croatia) Estuaries: A Comparative Study - You-You Hao; Zhuo-Yi Zhu; Fu-Tao Fang; Tihana Novak; Milan Čanković; Enis Hrustić; Zrinka Ljubešić; Ming Li; Jin-Zhou Du; Rui-Feng Zhang; Blaženka Gašparović (Frontiers in Marine Science, 2021)
Estuaries modify the concentration and composition of riverine nutrients and organic matter (OM), which eventually determine the riverine flux effect to coasts. Nutrients, organic carbon (OC), pigments, and amino acids (AAs) from the samples collected in the eutrophic Wenchang River Estuary (WRE) in China and the oligotrophic Krka River Estuary (KRE) in Croatia were analyzed in order to have a better understanding of how estuaries regulate terrestrial materials. We found a clear increase of dissolved inorganic nitrogen (DIN) concentration and its subsequent decrease due to the removal of DIN (over 100 μM) in the WRE, whereas DIN showed minor variation lengthwise in the KRE, i.e., with the salinity changes, ranging between 1.0 and 5.8 μM. The elevated algae-derived OC, dissolved organic nitrogen, and particulate AAs nitrogen suggest that the OM assimilation may explain approximately one-third of the DIN removal in the WRE, whereas in the oligotrophic KRE, such inorganic to organic transformation is not likely to be significant. Due to the prominent estuarine nitrogen removal/assimilation process, DIN/dissolved inorganic phosphorus (DIP) ratio was as high as 425 in the upper WRE under strong riverine influence, but it declined to as low as 5.4 at the mouth of WRE, that is even lower than DIN/DIP ratio at the mouth of oligotrophic KRE (12). When compared with other rivers worldwide, the Wenchang River showed high nutrients and organic carbon yields. Given the contrasting estuarine process (e.g., DIN removal) between the KRE and the WRE, apparent high nutrient yield from eutrophic rivers should be viewed with caution in ocean studies as the final impact to coastal zone could be similar to the oligotrophic rivers like the KRE.

Fast and accurate detection of kiwifruit in orchard using improved YOLOv3-tiny model - Longsheng Fu; Yali Feng; Jingzhu Wu; Zhihao Liu; Fangfang Gao; Yaqoob Majeed; Ahmad Al-Mallahi; Qin Zhang; Rui Li; Yongjie Cui (Precision Agriculture, 2021)

Systematic analysis of differentially expressed ZmMYB genes related to drought stress in maize - Peng-Yu Zhang; Xiao Qiu; Jia-Xu Fu; Guo-Rui Wang; Li Wei; Tong-Chao Wang (Physiology and Molecular Biology of Plants, 2021)

High-resolution estimation of ambient sulfate concentration over Taiwan Island using a novel ensemble machine-learning model - Lulu Cui; Qingwei Ma; Rui Li; Hongbo Fu; Ziyu Zhang; Liwu Zhang; Ying Chen (Environmental Science and Pollution Research, 2021)

Genetic diversity and population structure of Tibetan sheep breeds determined by whole genome resequencing - Lei-Lei Li; Shi-Ke Ma; Wei Peng; You-Gui Fang; Hai-Rui Duo; Hong-Yun Fu; Gong-Xue Jia (Tropical Animal Health and Production, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

Genetic and clinical determinants of mizoribine pharmacokinetics in renal transplant recipients - Rui Dai; Jingjie Li; Jingjing Wu; Qian Fu; Jiajia Yan; Guoping Zhong; Changxi Wang; Xiao Chen; Pan Chen (European Journal of Clinical Pharmacology, 2021)